Molecular cause and functional impact of altered synaptic lipid signaling due to a prg‐1 gene SNP. Issue 1 (15th December 2015) - Vogt, Johannes; Yang, Jenq‐Wei; Mobascher, Arian; Cheng, Jin; Li, Yunbo; Liu, Xingfeng; Baumgart, Jan; Thalman, Carine; Kirischuk, Sergei; Unichenko, Petr; Horta, Guilherme; Radyushkin, Konstantin; et al.
Abstract: Loss of plasticity‐related gene 1 (PRG‐1), which regulates synaptic phospholipid signaling, leads to hyperexcitability via increased glutamate release altering excitation/inhibition (E/I) balance in cortical networks. A recently reported SNP in prg‐1 (R345T/mutPRG‐1) affects ~5 million European and US citizens in a monoallelic variant. Our studies show that this mutation leads to a loss‐of‐PRG‐1 function at the synapse due to its inability to control lysophosphatidic acid (LPA) levels via a cellular uptake mechanism which appears to depend on proper glycosylation altered by this SNP. PRG‐1 +/− mice, which are animal correlates of human PRG‐1 +/mut carriers, showed an altered cortical network function and stress‐related behavioral changes indicating altered resilience against psychiatric disorders. These could be reversed by modulation of phospholipid signaling via pharmacological inhibition of the LPA‐synthesizing molecule autotaxin. In line, EEG recordings in a human population‐based cohort revealed an E/I balance shift in monoallelic mutPRG‐1 carriers and an impaired sensory gating, which is regarded as an endophenotype of stress‐related mental disorders. Intervention into bioactive lipid signaling is thus a promising strategy to interfere with glutamate‐dependent symptoms in psychiatric diseases. Synopsis: Synaptic phospholipids are potent bioactive factors known to increase glutamatergic transmission in excitatory neurons, and they are normally cleared from the synaptic cleft by PRG‐1. A common loss‐of‐function SNP in PRG‐1 affects the pathophysiology and behavior in a way reminiscent of psychiatric disorders. The human PRG‐1 SNP (R345T), present in a monoallelic variant, abolished PRG‐1 function by impeding its ability for LPA internalization due to altered glycosylation. Monoallelic PRG‐1 deficiency affected cortical information processing, leading to decreased somatosensory filter function in rodents and humans, and impaired resilience during stress‐related behaviors, an endophenotype of psychiatric disorders. Pharmacological intervention specifically targeting phospholipid signaling rescued cortical somatosensory filter function to wild‐type levels, opening a new therapeutic perspective for stress‐related mental dysfunctions. Abstract : Synaptic phospholipids are potent bioactive factors known to increase glutamatergic transmission in excitatory neurons, and they are normally cleared from the synaptic cleft by PRG‐1. A common loss‐of‐function SNP in PRG‐1 affects the pathophysiology and behavior in a way reminiscent of psychiatric disorders.